2022
DOI: 10.1259/bjrcr.20210035
|View full text |Cite
|
Sign up to set email alerts
|

“Worm within worm”: acute appendicitis containing an adult Ascaris lumbricoïdes

Abstract: Appendicitis is the first aetiology for abdominal surgical emergency. Ascariasis is the most common helminth infection in tropical countries where it is endemic. The ability of intestinal helminths to wander through the digestive system means that it can end up in the appendix lumen and lead to appendicitis by luminal obstruction. However, this presentation is still rarely described in the literature. In fact, most of the diagnoses of roundworm associated with appendicitis are made retrospectively by the disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The involvement of Ascaris lumbricoides , a common intestinal parasite, in causing appendicitis is controversial; while it can migrate to the appendix, mimicking appendicitis symptoms, its role as a direct causative agent remains unclear [ 5 ]. Suspected appendicitis due to roundworm is commonly confirmed through the identification of roundworm eggs in the appendectomy specimen [ 6 ]. Wani et al found in their study that while 72.7% of patients with Ascaris lumbricoides underwent surgical treatment, only 27.2% showed histopathological evidence of appendicitis linked to Ascaris lumbricoides [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of Ascaris lumbricoides , a common intestinal parasite, in causing appendicitis is controversial; while it can migrate to the appendix, mimicking appendicitis symptoms, its role as a direct causative agent remains unclear [ 5 ]. Suspected appendicitis due to roundworm is commonly confirmed through the identification of roundworm eggs in the appendectomy specimen [ 6 ]. Wani et al found in their study that while 72.7% of patients with Ascaris lumbricoides underwent surgical treatment, only 27.2% showed histopathological evidence of appendicitis linked to Ascaris lumbricoides [ 7 ].…”
Section: Introductionmentioning
confidence: 99%